MAPK signalling pathway in cancers: Olive products as cancer preventive and therapeutic agents. (June 2019) - Peluso, Ilaria; Yarla, Nagendra Sastry; Ambra, Roberto; Pastore, Gianni; Perry, George
Abstract: The mitogen-activated protein kinases (MAPKs) are fundamental in inflammation and cancer control, through the crosstalk between the redox regulated nuclear factor E2-related factor 2 (Nrf2) and nuclear factor-kB (NFκB) gene expression. MAPKs regulate various cellular activities involved in cancer progression, including proliferation, apoptosis and immune escape and blockade of upstream kinases is a current therapeutic strategy. However, these therapies are associated with some adverse effects and with the paradoxical activation of the MAPKs pathway. In the context of cancer prevention and treatment, it has been suggested that dietary factors are able to modulate cancer initiation and progression by interacting with the MAPKs. Within these dietary factors, virgin olive oil (VOO) is of particular interest due to its content in squalene, already used as drug delivery system in cancer therapy. The aim of this review is to discuss the studies pointing to the effects of olive-derived foodstuff and nutraceuticals on MAPKs signalling cascades. The reviewed experimental studies suggest that the stress-activated JNK and p38 MAPKs could be targets of olive-derived nutraceuticals. The latter, including phytochemicals from olive cultivation and processing wastes, could be adjuvants in chemotherapies, whereas VOO could be considered a "natural delivery system" of bioactive phytochemicals due to its high content in squalene.